Pengaruh Pendidikan Lingkungan Hidup Terhadap Sikap Peduli Lingkungan Siswa di SD Nasional KPS Balikpapan - Ariyanti, Della; Mohammad Baihaqi (Institut Agama Islam Negeri Palangka Raya, 2025)
Environmental degradation continues to escalate globally, underscoring the urgent need to enhance environmental education from the earliest stages of schooling. This study aims to examine the influence of Environmental Education (Pendidikan Lingkungan Hidup: PLH) on the environmental care attitudes of fifth-grade students at SD Nasional KPS Balikpapan. A quantitative correlational design was employed, involving 30 students selected through a total sampling approach. A Likert-scale questionnaire was used and validated prior to analysis, employing simple linear regression. The results indicate that PLH has a positive yet statistically insignificant influence on students' environmental care attitudes (β = 0.234; p = 0.086). The R² value of 0.102 shows that PLH contributes only 10.2% to the variance in environmental care attitudes. In contrast, the remaining 89.8% is influenced by other factors such as school culture, family environment, and peer interactions. These findings suggest that PLH at the elementary level must be strengthened through more holistic, experiential, and contextually integrated approaches that support the development of environmentally responsible behavior.